2018
DOI: 10.1155/2018/2156980
|View full text |Cite
|
Sign up to set email alerts
|

EPS Current Tracking Method Research Based on Hybrid Sensitivity H Control Algorithm

Abstract: For electric power steering system (EPS), road interference, noise of the sensor, and the uncertainty of the steering system may make EPS control effect and the driver's road sense worse. EPS system which takes advantage of good current tracking ability, good anti-interference ability, and good operation stability is becoming more and more important in automotive research. The traditional H ∞ control algorithm can solve the system uncertainty theoretically, but it cannot solve the contradiction between robustn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Substitute expressions (18) and (20) into the inequality equation (31) to get the following linear inequality PÃ + PBK +Ã T P + K TB T P PB w I B T w P…”
Section: Controller Design Based On Lmi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitute expressions (18) and (20) into the inequality equation (31) to get the following linear inequality PÃ + PBK +Ã T P + K TB T P PB w I B T w P…”
Section: Controller Design Based On Lmi Methodsmentioning
confidence: 99%
“…The PXI-based HIL test bench is built which is shown in the Figure 6 and the bench is built according to Wu et al 31 The designed controller and relevant model and experimental actuator can be combined dynamically in real time and be easy for signal transmission. It is convenient to get the active steering controller with both performance and robustness by setting various conditions and adjusting parameters of the controller.…”
Section: Hil Test Implementationmentioning
confidence: 99%
“…Under the condition of in situ simulation, the hand torque is applied on the steering wheel, and the dSPACE software console records the actual current to the target current data under different conditions in real time. e tracking effect between the actual torque and the target torque and between the actual current and the target current is analyzed [26], and then the performance of the controller is verified. e hardware in the loop test results are shown in Figures 13 and 14.…”
Section: Hardware In the Loop Testmentioning
confidence: 99%
“…Xu et al. 8 focused on the current tracking of EPS motors, proposed a H ∞ control strategy with mixed sensitivity based on the road interference and noise of the sensor, and carried out simulation and bench experiments, which showed that it was able to achieve fast response of the EPS as well as remove noise from both road and sensor. Both Lee et al.…”
Section: Introductionmentioning
confidence: 99%